The Effect of Cooperative Integrated Reading Composition (CIRC) on Studentsâ Reading Comprehension of Essay at English Study Program of University of Pasir Pengaraian - Donal, Andri; Niati, Batdal (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
Essay is the most important part learned and comprehended by sixth semester students of English study program of University of Pasir Pengaraian. Even though essay is not subject, however it is essential part of writing and reading. It is learned in critical essay. Thus, to improve their skill, a research was needed.The purpose of this research was to investigate whether students who were taught by Cooperative Integrated Reading Composition (CIRC) have better reading comprehension of essay than those who were taught by small group discussion.This research was quasi experimental research. It was nonequivalent control group design; post-test only design. The treatments were only done in experimental class while control class was taught as usual. Population and sample of this research were same. It consists of two classes. They were thirty nine students. Control class is taught by small group discussion and experimental class is taught by cooperative integrated reading composition (CIRC). Reading comprehension test; essay question form was used to collect the data. The data were analyzed by using independent t-test. The finding was students who are taught by cooperative integrated reading composition (CIRC) have better scores (comprehension well) than those who are taught by small group discussion. The finding enrichs theories about technique in teaching critical essay subject.